Snakes' Legs Sequels, Continuations, Rewritings, and Chinese Fiction - Chen Hu, Siao; Hegel, Robert; Huang, Martin W.; Huang, Martin; Laura Wu, H.; Li, Qiancheng; Mcmahon, Keith; Wang, Ying; Widmer, Ellen; Yang, Shuhui (University of Hawaii Press, 2004)
Snakes' Legs examines sequels (xushu), a common but long-neglected literary phenomenon in traditional China. What prompted writers to produce sequels despite their poor reputation as a genre? What motivated readers to read them? How should we characterize the nature of the relationship between sequels and rewritings? Contributors to this volume illuminate these and other questions, and the collection as a whole offers a comprehensive consideration of this vigorous genre while suggesting fascinating new directions for research. Xushu as a discursive practice reinforces the paradox that innovation is impossible without imitation. It presents us with fertile ground for studying the intricate ties that bind the writer and reader of traditional Chinese fiction: the writer of xushu is always self-consciously assuming the dual role of author and reader and in the writing process must consider both the work in progress as well as its precursor(s). Snakes' Legs contains detailed discussions of some representative xushu works from the late Ming and Qing periods, many of which have received little scholarly attention. It will shed light on the development of Chinese fiction and the various textual practices in traditional China as well as account for the genre's continuing vitality in modern times. Contributors: Robert E. Hegel, Siao-chen Hu, Martin W. Huang, Keith McMahon, Qiancheng Li, Ying Wang, Ellen Widmer, Laura H. Wu, Shuhui Yang